A general finite volume method for the solution of the reynolds lubrication equation with a mass-conserving cavitation model - Profito,FJ; Giacopini,M; Zachariadis,DC; Dini,D (Tribology Letters, 2015)
This contribution presents the development of a general discretization scheme for the solution of Reynolds equation with a mass-conserving cavitation model and its application for the numerical simulation of lubricated contacts to be discretized using irregular grids. Such scheme is based on a hybrid-type formulation, here named as element-based finite volume method that combines the flexibility of the FEM to deal with unstructured grids, while preserving the local and global fluid-flow conservation aspect of the FVM throughout the discretized domain. The accuracy and robustness of the method are successfully tested using several benchmark cases proposed in the recent literature. Simulations of fully or partially textured sliding bearings are finally employed to show the advantages of being able to adopt irregular meshes both in terms of flexibility for the discretization of complex surface features and computational speed.